On the Fire Hazard of High-Rise Buildings and Skyscrapers - I. S. Taubkin (Теория и практика судебной экспертизы, 2024)
The article presents an analysis of fire hazard of high-rise buildings and skyscrapers. The author notes a range of factors significantly impacting on the course of emergency rescue operations, including the difficulty of evacuating people from the burning buildings (e.g., due to the rapid movement of combustion products to the roof of the building, the duration of the descent down the stairs to evacuation exits, etc.), uncertainty of toxicity (the nature of gases formed during combustion, the synergism of their toxic effect, the determination of toxic dose), difficulties in rescuing people from the upper floors of the building and in the process of extinguishing a fire (due to the lack of necessary fire equipment), as well as the behavior of people caught in a fire in the building. The inadmissibility of using «risk-analysis» in the forensic practice is emphasized, since the correct initial data (linear and mass burning rates) for its calculation is unknown. The article is intended for fire experts of the forensic institutions of various departments, investigators of the Ministry of Emergency Situations and employees of engineering organizations.